Thermodynamic simulation and damage analysis of magnesium production retort tubes. (October 2020) - Maarefvand, Majid; Sadeghi, Alireza; Nazari-Onlaghi, Sina
Highlights: Microstructures of a retort are precisely investigated before and after failure. Grain growth, decarburization & precipitate dissolution occurs in retorts. Si-rich precipitates are formed around the macro-cracks. A stringer of precipitates is formed, along the circumferential direction at the mid-thickness. Newly formed precipitates prepare easy passage for crack growth. Abstract: Magnesium reduction retorts fail after 60 days of operation owing to the extreme operating conditions (1200 °C and internal vacuum). Understanding failure micro-mechanisms is vital to designing new retorts with a prolonged lifespan. In this study, detailed thermodynamic simulation and microstructural examination are presented for creep failure analysis of retorts. Through thermodynamic simulations, the effect of C depletion and increase of Si concentration on equilibrium phases were studied. Microstructural evolutions are classified into three categories; (1) nucleation and propagation of surface and internal cracks, (2) formation of new precipitates, and (3) decomposition of austenite to pearlite in specific regions. Grain structures and second phases are linked to thermodynamic calculations and local chemical analysis by EDS in SEM. The controlling parameters of microstructural damages of retort tubes are studied systematically and summarized in this paper.